Crises of Identity - Mandelkern, Matthew (Proceedings of the Amsterdam Colloquium, 2019)
Identity says that any conditional with the form ⌜If p, then p⌝ is a logical truth. I show that a wide range of theories invalidate Identity. I argue this is due to a tension between Identity and Import-Export, and sketch a potential solution.